WOMEN’S RESISTANCE TO GENDER INJUSTICE IN DIAN PURNOMO’S NOVEL PEREMPUAN YANG MENANGIS KEPADA BULAN HITAM - Nurbayti; Kurnia Rachmawati; Arju Susanto (Program Studi Pendidikan Bahasa dan Sastra Indonesia, FKIP, Universitas Halu Oleo Kampus Bumi Tridharma Andounohu Kendari, Provinsi Sulawesi Tenggara – Indonesia, 2023)
Gender injustice experienced by women and written by women in the novel Perempuan yang Menangis kepada Bulan Hitam by Dian Purnomo. This study aims to describe the form of gender injustice problems to resistance to patriarchal culture. This research method uses qualitative descriptive methods that produce data in the form of observable words, sentences, and expressions. This research was studied with a literary feminism approach using Mansour Fakih's gender injustice theory and feminism theory. The data collection technique used is a reading and recording technique. The discussion focused on gender injustice caused by a patriarchal culture that has been inherent in people's lives. Sumba culture—about the tradition of “kawin tangkap” (capture and wed) which has been preserved until now has reflected this and how Magi Diela fought against the injustice she experienced. The results of this study show forms of gender injustice in the form of marginalization, subordination, stereotypes, violence, and workload. This injustice encourages women to fight for their independence, existence, and abilities of women.